2007
DOI: 10.2190/mr65-2605-1285-0406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an International Embargo on Malnutrition and Childhood Mortality in Rural Haiti

Abstract: The study objective was to determine the effect of an international embargo against Haiti, from October 1991 through October 1994, on early childhood protein-energy malnutrition and all-cause mortality in a geographic area where humanitarian aid was continuously available to the children in the study. The authors used longitudinal anthropometric records on 1593 children, 24 months old or younger, living in the rural Grand Anse Department of Haiti from 1989 through 1996. Kaplan-Meier graphs for all-cause mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…This was also consistent with the literature conducted in other settings [82,83], which found that supplement-based interventions, specifically ready-to-use supplementary food, were effective in improving markers of anaemia, and wasting among children under 5 years of age [82,83]. Similar to the interventions discussed above, most authors highlighted that scarce resources were a major limitation within these settings [28,31,32,38,71]. One of the included studies specifically highlighted the success of an intervention that used micronutrient powder distributed by microfinance institutions [25].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This was also consistent with the literature conducted in other settings [82,83], which found that supplement-based interventions, specifically ready-to-use supplementary food, were effective in improving markers of anaemia, and wasting among children under 5 years of age [82,83]. Similar to the interventions discussed above, most authors highlighted that scarce resources were a major limitation within these settings [28,31,32,38,71]. One of the included studies specifically highlighted the success of an intervention that used micronutrient powder distributed by microfinance institutions [25].…”
Section: Discussionsupporting
confidence: 85%
“…Studies were conducted in seventeen countries. Twenty-four studies were conducted in the Caribbean: nine in Haiti [25][26][27][28][29][30][31][32][33], three in Cuba [34][35][36], three in Dominican Republic [37][38][39], three in Jamaica [24,40,41], three in Trinidad and Tobago [42][43][44], two in Puerto Rico [45,46] and one in Barbados [47]. Eighteen studies were conducted in the Atlantic, Indian Ocean, Mediterranean and South China Sea (AIMS region): fifteen in Singapore [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62], two in Mauritius [63,64] and one in Seychelles [65].…”
Section: Location and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 80 percent of the rural population lives in poverty, and their life expectancy is only 54 years. The poverty level is also reflected in the prevalence of malnutrition; approximately half of children under 5 years of age experience some level of malnutrition .…”
Section: Introductionmentioning
confidence: 99%